Effects of plasma treatment on the sorption properties of coconut fibers - De Oliveira, Daniel Magalhães [UNESP]; Hilário Cioffi, Maria Odila [UNESP]; De Carvalho Benini, Kelly Cristina Coelho [UNESP]; Cornelis Voorwald, Herman Jacobus [UNESP] (Elsevier, 2017)
This work compares the effects of plasma treatment on the sorption capacity of untreated and treated coconut fibers. Non-woven mats of coconut fibers were firstly molded by hand, than washed with boiling water, dried, and finally treated by argon plasma jet. Treated and untreated coconut fibers mats have been analyzed by the absorption and contact angle measurements, besides the scanning electron microscopy (SEM) analysis. These characterizations show that the plasma treatment provides to coconut fibers an increase in hydrophilicity and surface roughness, enabling them better sorption properties.
Keywords: Coconut fibers; plasma treatment; sorption properties